(untitled) (Web of Teachers: Inderscience Research, 2024)
Corpus linguistics has emerged as a pivotal tool in modern education, providing insights into language patterns, authentic usage, and learner errors. This paper explores the methodologies and approaches applied in educational contexts, highlighting the significance of corpora in teaching grammar, vocabulary, and writing skills. By leveraging linguistic data from large text collections, educators can enhance lesson plans, foster learner autonomy, and encourage data-driven learning. The article delves into the integration of corpus tools in curriculum design and language assessment, promoting empirical and evidence-based teaching practices.